A clinical approach to diagnosis of autoimmune encephalitis. Issue 4 (April 2016) - Graus, Francesc; Titulaer, Maarten J; Balu, Ramani; Benseler, Susanne; Bien, Christian G; Cellucci, Tania; Cortese, Irene; Dale, Russell C; Gelfand, Jeffrey M; Geschwind, Michael; Glaser, Carol A; Honnorat, Jerome; et al.
Summary: Encephalitis is a severe inflammatory disorder of the brain with many possible causes and a complex differential diagnosis. Advances in autoimmune encephalitis research in the past 10 years have led to the identification of new syndromes and biomarkers that have transformed the diagnostic approach to these disorders. However, existing criteria for autoimmune encephalitis are too reliant on antibody testing and response to immunotherapy, which might delay the diagnosis. We reviewed the literature and gathered the experience of a team of experts with the aims of developing a practical, syndrome-based diagnostic approach to autoimmune encephalitis and providing guidelines to navigate through the differential diagnosis. Because autoantibody test results and response to therapy are not available at disease onset, we based the initial diagnostic approach on neurological assessment and conventional tests that are accessible to most clinicians. Through logical differential diagnosis, levels of evidence for autoimmune encephalitis (possible, probable, or definite) are achieved, which can lead to prompt immunotherapy.